A reference grammar of Waray - Madeja, Jovito B. (Animo Repository, 2017)
The study explicates the grammar of Waray using . Since this study is considered the first to describe the intricacies of Waray grammar, some discussions are limited to the usage with an attempt to discuss its linguistic features in the best possible way. Though there were few studies conducted in Waray, this study is the first in-depth investigation of Waray. This study used some data from Dita (2010b), Madeja (2012a, 2012b), and Santos (2012). Those data from Santos (2012) were translated to Waray since Hiligaynon and Waray share same similarities. Other data sources used in this study are the informants, the participants, and the consultants being native speakers of Waray. Since, Santos (2012) is a description of Hiligaynon which is a language similar to Waray, models on morphology, syntax, and ergative pattern of sentence analysis in its description were used. While, phonology is simply described based on the analysis of the informants and the researcher. Specifically, the study's objective is to describe the grammar of Waray in terms of Phonology, Morphology, Nominal Markers, Pronominals, Nominals, Verbs, Adverbs, Adjectives, Numerals, Connectors, and Interrogatives.This reference grammar of Waray is comprised of 14 chapters. Chapter 1 provides the introduction, which includes the background of the study, background of Waray as a Visayan language, background of Philippine linguistics, synthesis and research gap, objective of the study, theoretical frameworks, and significance of the study, while Chapter 2 presents the methodology of the study, which includes the participants/informants, materials/sources, outline of the study, and procedure and analysis.After presenting the introduction and methodology of the study, Chapter 3 discusses the components of the grammar of Waray. In this chapter, the phonology of Waray, which includes the consonants and vowels, is discussed. The manner of articulation is divided into stop, fricative, nasal, lateral, flap and glides. The place of articulation is also divided as bilabial, labio-dental, alveolar, palatal, and velar, and glottal. In Chapter 4, the morphology is described. It is made clear in this chapter that the researcher subscribes to the idea that there is no clear-cut classification of words or parts of the words into nouns, adjectives, and verbs. Instead, like other Philippine languages, the interrelationship among roots, affixes, and particles and their use in the discourse determine their classification. This chapter also discusses noun, adjectives, and verb formation through CV and full reduplication, and it is found that the stem-based affixation is useful in simplifying the complex affixation system observed in the formation of Waray nouns, adjectives, and verbs. Chapter 5 presents the nominal marking systems, specifically the determiners and demontratives in Waray. Like other Philippine languages, determiners in Waray encode number (singular and plural), case (absolutive, ergative/genitive, and oblique/locative), and distinguish between common and personal nouns. Furthermore, the section shows that ha also works as a temporal indicator of present and future time. Chapter 6 discusses the pronominal system of Waray. Two categories of pronominals are presented: personal pronouns and demonstratives. There are four gramamtical functions of pronouns that are further discussed in this chapter: the absolutives, the ergatives, the genitives and possessives, and the obliques. As for the demonstratives, the three degrees of orientation (proximal, medial, and distal) are exemplified. The next chapter, Chapter 7, discusses the plurality that takes place in nouns through the use of the common noun determiner mga and the stem-forming affix ka-, like in other Philippine languages. These, in addition, provide examples of the stem- based affixation to form nouns in Waray. This chapter further shows examples of borrowed nouns found in the language, specifically from Spanish and English. What follows is the detailed discussion of Verbs in Chapter 8. As the case in Philippine languages, Chapter 8 specifically includes the focuses, aspects, and classes of Waray verbs. This classification of words is also shown through the stem-based affixation. Some other verb classes were also given emphasis in this chapter particularly the stative verbs, inchoative verbs, process verbs, grooming verbs, motion verbs, body posture verbs, birectional verbs, reciprocal verbs, activity verbs, pretense verbs, utterance verbs, perception verbs, emotion verbs, cognition verbs and nag- verbs. Chapter 9 presents the five categories of adjectives: degrees of gradation; affixation; syntactic properties; and semantic properties. Like in other Philippine languages, Waray adjectives are observed to be used as predicate adjectives with a pronominal complement and with an NP, attributive adjectives, moderate intensification and intensive intensification, and the comparative and superlative degrees of gradation. The section on morphological properties of adjectives shows sentences that exemplify bare or un-affixed. This chapter also provides illustrations of the semantic properties of adjectives that include the following: dimension; physical property; value; color; human propensity; speed, quantification, age and difficulty; and position, qualification, and similarity.Chapter 10 focuses in expounding the Waray lexical particles and adjuncts. The definitions and corresponding sample sentences which encompass the various categories of the lexical particles are modal, temporal, limiting, and emphatic. These are shown in the first part of this chapter. Chapter 10 also explains the manner, locative, temporal, frequency and simultaneity, all of which are categories of adjuncts. Additionally, Chapter 11 presents the different numeral xxii expressions in Waray, which are used today, specifically the cardinals, ordinal distributives, and multiplicative. This chapter further explains the morphological and syntactic properties of the numerals of the language and the long numerals, which generally function as nominal modifiers and adjuncts.Next, Chapter 12 illustrates connectors in Waray. Similar to some Philippine languages, the use of grammatical particles or ligatures is important in Waray language for they conjoin modifiers or specifiers to the subject. These ligatures or grammatical particles are ka, and nga. These connectors show how to use the different coordinators/conjunctions of Waray in divergent, convergent, and co-occuring conditions. Then, Chapter 13 discusses and presents several categories of Waray interrogatives that consist of the Yes/No, the Alternative, the Confirmation, and the Information questions. Finally, Chapter 14 presents the summary with the conclusion and the research opportunities in Waray.